Growth improvement of wheat (Triticum aestivum) and zinc biofortification using potent zinc-solubilizing bacteria - Ali, Murad; Ahmed, Iftikhar; Tariq, Hamza; Abbas, Saira; Zia, Munir Hussain; Mumtaz, Amer; Sharif, Muhammad (Frontiers in Plant Science, 2023)
Zinc (Zn) is an indispensable element for proper plant growth. A sizeable proportion of the inorganic Zn that is added to soil undergoes a transformation into an insoluble form. Zinc-solubilizing bacteria (ZSB) have the potential to transform the insoluble Zn into plant-accessible forms and are thus promising alternatives for Zn supplementation. The current research was aimed at investigating the Zn solubilization potential of indigenous bacterial strains and to evaluate their impact on wheat growth and Zn biofortification. A number of experiments were conducted at the National Agriculture Research Center (NARC), Islamabad, during 2020-21. A total of 69 strains were assessed for their Zn-solubilizing ability against two insoluble Zn sources (ZnO and ZnCO3) using plate assay techniques. During the qualitative assay, the solubilization index and solubilization efficiency were measured. The qualitatively selected Zn-solubilizing bacterial strains were further tested quantitatively using broth culture for Zn and phosphorus (P) solubility. Tricalcium phosphate was used as insoluble source of P. The results showed that broth culture pH was negatively correlated with Zn solubilization, i.e., ZnO (r2 = 0.88) and ZnCO3 (r2 = 0.96). Ten novel promising strains, i.e., Pantoea sp. NCCP-525, Klebsiella sp. NCCP-607, Brevibacterium sp. NCCP-622, Klebsiella sp. NCCP-623, Acinetobacter sp. NCCP-644, Alcaligenes sp. NCCP-650, Citrobacter sp. NCCP-668, Exiguobacterium sp. NCCP-673, Raoultella sp. NCCP-675, and Acinetobacter sp. NCCP-680, were selected from the ecology of Pakistan for further experimentation on wheat crop based on plant growth-promoting rhizobacteria (PGPR) traits, i.e., solubilization of Zn and P in addition to being positive for nifH and acdS genes. Before evaluating the bacterial strains for plant growth potential, a control experiment was also conducted to determine the highest critical Zn level from ZnO to wheat growth using different Zn levels (0.1, 0.05, 0.01, 0.005, and 0.001% Zn) against two wheat varieties (Wadaan-17 and Zincol-16) in sand culture under glasshouse conditions. Zinc-free Hoagland nutrients solution was used to irrigate the wheat plants. As a result, 50 mg kg-1 of Zn from ZnO was identified as the highest critical level for wheat growth. Using the critical level (50 mg kg-1 of Zn), the selected ZSB strains were inoculated alone and in consortium to the seed of wheat, with and without the use of ZnO, in sterilized sand culture. The ZSB inoculation in consortium without ZnO resulted in improved shoot length (14%), shoot fresh weight (34%), and shoot dry weight (37%); with ZnO root length (116%), it saw root fresh weight (435%), root dry weight (435%), and Zn content in the shoot (1177%) as compared to the control. Wadaan-17 performed better on growth attributes, while Zincol-16 had 5% more shoot Zn concentration. The present study concluded that the selected bacterial strains show the potential to act as ZSB and are highly efficient bio-inoculants to combat Zn deficiency, and the inoculation of these strains in consortium performed better in terms of growth and Zn solubility for wheat as compared to individual inoculation. The study further concluded that 50 mg kg-1 Zn from ZnO had no negative impact on wheat growth; however, higher concentrations hampered wheat growth.